2015
DOI: 10.1016/j.jchf.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Long-Term Outcomes After Septal Reduction Therapy in Patients With Hypertrophic Cardiomyopathy

Abstract: Long-term mortality and (aborted) SCD rates after ASA and myectomy are similarly low. Patients who undergo ASA have more than twice the risk of permanent pacemaker implantation and a 5 times higher risk of the need for additional septal reduction therapy compared with those who undergo myectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 56 publications
5
123
1
5
Order By: Relevance
“…Sorajja et al reported comparable survival between ASA and surgical myectomy, without an increased risk of sudden death; however, the reintervention rate for ASA was significantly higher (43). Similar results were reported by Liebregts et al in a recent meta-analysis as well as other single-center studies (55,56). Conversely, Cate et al reported a five-fold increase in the incidence of cardiac death and arrhythmic complications after ASA as compared to myectomy (50), and Vriesendorp et al still reported a slight increase in sudden cardiac death after ASA when compared to myectomy (57).…”
Section: Ablation Versus Myectomysupporting
confidence: 69%
“…Sorajja et al reported comparable survival between ASA and surgical myectomy, without an increased risk of sudden death; however, the reintervention rate for ASA was significantly higher (43). Similar results were reported by Liebregts et al in a recent meta-analysis as well as other single-center studies (55,56). Conversely, Cate et al reported a five-fold increase in the incidence of cardiac death and arrhythmic complications after ASA as compared to myectomy (50), and Vriesendorp et al still reported a slight increase in sudden cardiac death after ASA when compared to myectomy (57).…”
Section: Ablation Versus Myectomysupporting
confidence: 69%
“…In particular, alcohol ablation requires a shorter hospital admission and recovery time than surgery and is associated with less postoperative disability. In the last decade, a large body of literature (including a number of meta-analyses) has reported the results of this procedure (13,(22)(23)(24)(25)(26). Alcohol septal ablation can often relieve obstruction and improve symptoms (at least during an intermediate period of follow-up) when performed in properly selected patients by interventional cardiovascular specialists with extensive experience with this procedure (13,22,24,25).…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%
“…In the most recent registries (10,11), the percentage of patients who are lost at gradient/symptomatic follow-up or suffering obstruction requiring repeated SRT is 15-18%. Such numbers should be taken in serious considerations especially in view of the aforementioned limited follow-up in ASA and with the low rates of reoperation after septal myectomy that nowadays are well below 2% (21).…”
Section: Introductionmentioning
confidence: 99%